1992
DOI: 10.1080/00102209208951810
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study of the Gas Phase Oxidation of C6H5CI in a Flow Reactor

Abstract: The gas-phase. flameJess oxidation of chlorobenzcne (C 6H sCI) was studied experimentally in a 2. J cm 10 quartz flow-reactor operating at I atm pressure. Temperatures investigated were in the range 630-850°C, reaction times in the range 0.4-1.94 s, O 2 concentrations in the range 1.8-3.3% (fuel rich) at a fixed C, HsCI concentration of about 0.5% in Arcarrier gas. The absolute concentrations of the reactants and the products CO,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…This is consistent with the first-order pyrolysis model proposed by De Vissher et al for monocyclic aromatic compounds (). In addition, products characteristic of the reaction (carbon monoxide, carbon dioxide, acetylene, HCl) are gases obtained experimentally in gas-phase flameless oxidation of chlorobenzene ( , ).
5 4-ClPh, ClBz, and Cl - evolution with time.
…”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with the first-order pyrolysis model proposed by De Vissher et al for monocyclic aromatic compounds (). In addition, products characteristic of the reaction (carbon monoxide, carbon dioxide, acetylene, HCl) are gases obtained experimentally in gas-phase flameless oxidation of chlorobenzene ( , ).
5 4-ClPh, ClBz, and Cl - evolution with time.
…”
Section: Resultsmentioning
confidence: 99%
“…In a related study of the gas-phase oxidation of C 6 H 5 Cl, Senkan, Gutman, and co-workers suggested two different mechanisms for phenyl radical decomposition following chlorine atom cleavage . One mechanism is by β-scission of phenyl radical, and the other is a series of reactions after the oxidation of phenyl radical with the following mechanism: This ring-opening mechanism has not been further examined to determine whether it is an energetically viable pathway for the oxidation of benzene.…”
Section: Introductionmentioning
confidence: 99%